Pengembangan Kreativitas Anak melalui Kegiatan Loose Part Bertema Lingkungan Sekolah di TK Tunas Karya III Sukanagara - Eva Manfaaatin; Suci Nurul Pazri; Hera Siti Nurjanah; Yunira Yunda Riswanti (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2025)
Early childhood education plays a crucial role in building the foundation for children’s cognitive, social, emotional, and creative development. Creativity is an essential aspect that must be stimulated through meaningful and contextual play activities. This study aims to describe the process and outcomes of developing children’s creativity through the implementation of loose part play with the theme “School Environment” at TK Tunas Karya III Sukanagara. The research employed a descriptive qualitative approach involving 64 children from group A and group B, along with their accompanying teachers. Data were collected through participatory observation, semi-structured interviews, and documentation of the children’s creative works during the activities. The results reveal that loose part play effectively enhances children’s creativity. The children demonstrated improvements in divergent thinking, imagination, and self-confidence. Moreover, they became more environmentally aware, utilized recycled materials to create new objects, and exhibited collaboration and responsibility in group activities. Teachers played an essential role as facilitators who provided support and guidance throughout the exploration process. The loose part approach aligns with the principles of the Merdeka Curriculum, which emphasizes active, participatory, and experience-based learning for young children. This study provides practical implications for early childhood educators to design creative learning experiences that are low-cost, environmentally friendly, and relevant to the children’s real-life context.